Clinical Outcomes of Benzodiazepine Prescribing for People Receiving Opioid Agonist Treatment: A Systematic Review of the Evidence - Catriona Matheson; Chris Vucic; Josh Dumbrell; Roy Robertson; Trina Ritchie; Clare Duncan; Karthigayan Kessavalou; Caroline Woolston; Joe Schofield (MDPI AG, 2024)
Many countries are experiencing an increased use of unregulated benzodiazepines in combination with opioids and other drugs, which contributes to drug-related harm. This descriptive review identifies and synthesises the outcomes of studies co-prescribing benzodiazepines and opioids. A systematic review was undertaken in Medline, CINAHL, PsychInfo, Embase, and the Cochrane databases covering publications from 1 January 1991 to 18 November 2021. Inclusion criteria were peer reviewed, English language studies of adults prescribed opioid agonist treatment (OAT) and a concurrent benzodiazepine, and reporting outcome data. Of the 4370 titles screened, 18 papers were included. The main outcomes identified covered all-cause mortality (ACM) (n = 5); overdose death (n = 3); retention in treatment (n = 7); and hospitalisation/emergency department encounters (n = 2). Other outcomes included QTc interval, cognitive function, illicit drug use, and mental health. The prescription of benzodiazepines alongside OAT increased the ACM by 75-90%, while evidence on overdose death was less robust but indicative of increased risk (40-334%). There was an indicative positive effect on treatment retention, with increased retention in those prescribed a benzodiazepine with OAT compared to those not prescribed or taking non-prescribed benzodiazepines. In conclusion, methodologically robust epidemiological studies found increased ACM and overdose death but possibly improved retention. However confounders (e.g., psychiatric comorbidity) exist, so a trial is recommended.